TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK JASA SEWA TIKAR DI OBYEK WISATA PANTAI SENGGIGI (STUDY KASUS DESA SENGGIGI KECAMATAN BATULAYAR) - Siti Elva Helmawati; Parida Angriani (Nusantara Hasana Journal, 2024)
Rental research was carried out in the area of ​​Senggigi Beach, Senggigi Village, Batulayar Subdistrict, where the rental that occurred was unclear in carrying out the rental contract, especially in renting mats, because the terms and conditions that had to be in the rental had not been fulfilled, such as: both parties involved. carrying out a contract, consent and qabul in making a contract, goods/services being contracted, wages/payment for goods being contracted. In the field, the contract that took place was only known to one side, namely the merchant at that place, and then visitors assumed that the mat was a facility at that place because they had already bought it. In fact, the mats and snacks ordered are paid separately, visitors feel cheated by a contract like this. This research aims to discuss the practice of mat rental services at the Senggigi Beach tourist attraction, Batulayar district, and a review of sharia economic law regarding the practice of mat rental services at the Senggigi Beach tourist attraction, Batulayar district. This research uses a field research research method using a qualitative approach using descriptive data, namely data obtained from the field in the form of written and spoken words from people and the practice of mat rental services at the Senggigi beach tourist attraction, Senggigi Village, Batulayar District. Next, the researcher summarizes the results in the field to determine the focus of the research, the data is described in narrative form and draws conclusions to explain the findings based on an Islamic legal perspective. In practice, mat rental services for the Senggigi Beach tourist attraction are permitted under Islamic law. Because it can be said that both of them have fulfilled their rights and obligations as tenants and traders, and are pleased with each other regarding the contract which was not carried out at the beginning but was clarified at the end of the visit with the actual contract.